AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY IN SPEAKING ENGISH AT TENTH GRADE STUDENTS OF MAS RADHATUL AKMAL - INDRIYANTI, PUTRI (Faculty of Tarbiyah nad Teacher Training, 2022)
This research aimed to describe students’ anxiety in speaking English at tenth grade of MAS Raudhatul Akmal Batang Kuis. This study is intended to know the level of students’ anxiety and figure out what factors that may contribute to students’ anxiety in speaking English. This research used qualitative method with case study approach. The data collected from the observation, questionnaire, and interview. The questionnaire was developed by Horwitz and consists of 33 items with 5 point Likert-Scale. The result of this research showed that one student (5%) who experience anxious level, 11 students (61%) are in mildly anxious level, and 6 students (34%) students have relaxed level. And there are some factors in anxiety, students feel anxious when they are speaking in front of the class, they felt uneasy because all the students pay attention to them, being laughed at by others, fear of making mistake, unclear explanation and lack of preparation.